Resource Extraction and Regional Sustainability: An Economic Perspective on Water-Rock Interactions in Oil-Rich Areas - Yang, Runda (International Journal of Natural Resources and Environmental Studies, 2025)
Water-rock interactions play a critical role in shaping the geochemical and geomechanical characteristics of subsurface formations in oil-rich regions. Resource extraction in oil-rich regions significantly disrupts hydrogeological systems, particularly through water-rock interactions that affect long-term regional sustainability. The research adopts an economic perspective to assess the impact of oil extraction on subsurface geochemistry, focusing on the economic valuation of water degradation due to mineral dissolution, salinity shifts, and mobilization of trace elements. The operation is carried out using IBM SPSS software version 27.0, where multivariate regression analysis and t-tests are used to statistically model the relationship between extraction intensity, groundwater chemistry, and socio-economic outcomes across major oil-producing regions. The analysis incorporates time-series data on water quality indices, oil output, and regional economic indicators such as agricultural productivity loss, healthcare costs, and water treatment expenditures. Findings show a statistically significant correlation (p < 0.01) between increased extraction rates and elevated concentrations of sodium, chloride, and heavy metals in local aquifers. In high extraction zones, the average agricultural productivity is 2.34 tons/ha, while in low extraction zones it is 2.91 tons/ha (t = -4.73, df = 98, p < 0.001). Public health expenditure in high extraction areas averaged 124.7 USD/capita, compared to 89.3 USD/capita in low extraction areas (t = 5.16, df = 98, p < 0.001). The research defines regional sustainability as the balance between environmental protection, economic resilience, and social well-being in oil-rich areas, assessing groundwater degradation, economic losses, and community impact caused by water-rock interactions linked to oil extraction activities.